Kewartawanan warga di Malaysia: Satu kajian dari sudut pandangan wartawan warga = Citizen journalism in Malaysia: A study on local practitioner’s viewpoint - Balaraman, R.A.; Ibrahim, F.; Arokiasamy, L.; Mukhiar, S.N.S. (Universiti Kebangsaan Malaysia Press, 2016)
The development of the public acting as journalists has become a trend as a result of technological advances and easy internet access. Anyone with modern gadgets such as smartphones connected to the Internet are able to upload everything they capture, and call themselves citizen journalists! Does this concept correctly describe the Malaysian citizen journalists? What is citizen journalism? Who are citizen journalists and why do they exist in this country? This study will explore and answer questions about citizen journalism from the viewpoint of chosen local citizen journalists.